Inovasi Kebijakan Reduce-Reuse-Recycle (3R) dalam Penanganan Sampah Rumah Tangga di Kecamatan Sirimau - Jordeon Paulus Wakolle; Samson Laurens; Stanislaus Kostka Ohoiwutun (MAN 4 Kota Pekanbaru, 2026)
This article examines policy innovation in the implementation of Reduce-Reuse-Recycle (3R) principles for household waste management in Sirimau District, Ambon City. The study uses a qualitative descriptive-analytical approach based on in-depth interviews, participatory observation, and document analysis conducted from October 2024 to January 2025. Twenty-five informants were selected purposively from local government, community leaders, waste-bank managers, collectors, civil-society actors, and household representatives. The findings show that household waste management in Sirimau remains dominated by a conventional collect-transport-dispose model, while source separation and household-level waste reduction are still limited. Nevertheless, several innovations have emerged, including community-based digital waste banks, source-sorting pilots, multi-sector organic waste composting, household incentives, and environmental education grounded in local Maluku values. These innovations indicate that 3R policy cannot be treated merely as a technical waste-management instrument; it requires institutional coordination, community empowerment, economic incentives, and contextual adaptation to the geographic realities of an archipelagic city. The article argues that a locally embedded 3R model can strengthen circular-economy practices, reduce pressure on final disposal sites, and improve community participation when supported by consistent regulation, infrastructure, and cross-sector governance.